ALK-negative lung inflammatory myofibroblastic tumor in a young adult: A case report and literature review of molecular alterations. Issue 20 (21st May 2021) - Debonis, Silvia Angela; Bongiovanni, Alberto; Pieri, Federica; Fausti, Valentina; De Vita, Alessandro; Riva, Nada; Gurrieri, Lorena; Vanni, Silvia; Diano, Danila; Mercatali, Laura; Ibrahim, Toni
Abstract: Rationale: Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal tumor that is prevalent among children and adolescents. Surgery is the most important therapeutic approach for IMT and complete resection is recommended. Although 50% of IMTs show anaplastic lymphoma kinase (ALK) rearrangements, crizotinib has proven an effective therapeutic approach. However, the genetic landscape of this tumor is still not fully understood and treatment options are limited, especially in the majority of ALK-negative tumors. Patient concerns: We describe the clinical case of a healthy 18-year-old female in whom a pulmonary nodule was incidentally detected Diagnoses: Following a small increase in the size of the nodule, the patient underwent both 18 FDG-PET/CT and 68 Ga-PET/CT, resulting in a suspicion of bronchial hamartoma. Interventions: The patient underwent surgery and a salivary gland-like lung tumor was diagnosed. Outcomes: After surgery, the patient was referred to our cancer center, where a review of the histology slides gave a final diagnosis of ALK-negative lung IMT. Given the histology, it was decided not to administer adjuvant therapy and the patient was placed in a 3-monthly follow-up program. The patient is still disease-free 2 years post-surgery. Lessons: Although there is no standard of care for the treatment of IMT, identifying genomic alterations could help to redefine the management of patients with negative-ALK disease. Our review of the literature on IMT and other kinase fusions revealed, in addition to ALK rearrangements, the potential association of ROS1, NTRK, RET, or PDGFR beta alterations with the tumor. Abstract : Supplemental Digital Content is available in the text